Investigating the Deterring Factors for Youth Entrepreneurial Intention among Students at a South African University - Nsahlai, Veritas Kiyven; Zogli, Luther-King Junior; Lawa, Emmanuel; Dlamini, Bongani Innocent (Journal of Reviews on Global Economics, 2020)
Youth unemployment, which is a global phenomenon, is one of the main causes of poverty amongst the youth of South Africa. It has been observed that attaining a university qualification, no longer guarantees one an employment opportunity as the job market is highly saturated and cannot accommodate the thousands of young graduates churned out by universities each year. This leaves graduates with two options, either start a business or to remain unemployed and hope for an employment opportunity. This economic problem has led academics to inquire about what possible factors may influence young people to engage in entrepreneurship and what may turn them away from starting their own business. Although entrepreneurship has been purported globally as the springboard in facilitating economic participation among youth, they face many stumbling blocks during their entrepreneurial journey. The current study, therefore, sought to explore the factors that may deter youth entrepreneurial intention at a South African university. This is a quantitative research approach and data were collected using structured questionnaires from 247 participants and analysed using Factor analysis. It was discovered that lack of business management skills, risk and economic difficulties, financial challenges, lack of a support system, uncertain future and difficulty in finding partners, bureaucracy and crime as well as lack of relevant information were the factors deterring prospective young entrepreneurs from engaging in entrepreneurial activities.